PERUBAHAN TAMPILAN BUAH BERACUN MANGGA LAUT (Cerberra odollam) DAN KETERLIBATAN HYMENOPTERA DALAM PROSES DEKOMPOSISINYA - Salni, Hanifa Marisa, (SEMIRATA 2015, 2015)
A preliminary survey had been done on the change of C odollam fruits colour and size followed by the involve of some insects in those decomposition process. Survey take place at Pagar Alam, South Sumatera . on the end of 2014. Ten centimeters length of fruit with green colour and black spots fall down to ground after mature phase. Two Hymenoptera's found on the fruits that could be little black ant and litlle ichneumonid or small wasp. The fruit size looks chage to be smaller and the colour change to be red. These colour tend to change to brown and the outer layer released then. Seed in brown husk exposed to ground. Poisonous fruit for human was no danger to microbial and hymenoptera decomposer.Â Keywords: Cerberra odollam, poisonous fruit, ichneumonid, hymenoptera